Project Based Chemistry Learning on the Topic of Making Biodegradable Film from Corn Cobs: A Qualitative Content Analysis - Naila Azizah; Asep Supriatna; Triannisa Rahmawati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
Plastic waste has brought us an enormous environmental challenge. One solution that could be done to solve the problem of plastic waste is to switch to ordinary plastic using biodegradable film. Corn cob is a type of lignocellulosic waste. And it could be used as biodegradable film material. This research aims to construct a Teaching-Learning Sequence (TLS) in film formation from corn cobs. The Teaching-Learning Sequences (TLS) that were designed can be made into lesson plans or learning materials with the Project-Based Learning (PjBL) model that fits with the